(untitled) (Annals of Medical Research, 2023)
Aim: Retroperitoneal liposarcoma is a soft tissue malignancy that is typically seen as large mass lesions found incidentally on imaging. This study aimed to examine patients in light of clinicopathologic data and to investigate the reasons affecting recurrence and survival. Materials and Methods: A total of 32 patients with pathologically proven primary retroperitoneal liposarcoma who were treated between January 2011 and December 2021 were analyzed. Results: Thirty-two patients underwent surgery and all were treated with R0 resection. Recurrence was experienced by 12 (37.5%) patients and a further nine (28%) died during follow-up. The pathologic subtype of the tumor and the presence of fragmented specimens were found to be statistically significant with recurrence. Mortality was found to be high with 50% in patients with recurrence (p=0.049). Conclusions: Fragmented resection of retroperitoneal liposarcoma specimens is related to recurrence. The pathologic subtype of the tumor is significantly related to recurrence and overall survival. Additional chemotherapy or radiotherapy had no significant effect on recurrence or overall survival.